Tradurre o non tradurre il non standard? Una riflessione su "L’Arminuta" di Donatella Di Pietrantonio e la sua traduzione in norvegese - Thull, Pernille (Status Quaestionis, 2022)
The question we would like to ask goes beyond the well-known question of how to translate the non-standard, i.e., the strategies to be adopted, which we will deal with only in part (see especially Thull 2018). Rather, the more central question concerns the analysis of the writer’s intention when using a dialect or sociolect with a certain narrative function, which can vary greatly from author to author (Issa Mehawesh, 2014). In other words, what is the role of language code alternation (e.g., code mixing or code switching) in the structure of the text being translated? Should the presence of non-standard variant, and thus code- switching (in crosstalk or diatopy) always and in all cases be reproduced by the translator,or are there fairly clear cases in which it can be considered a secondary phenomenon from a semiotic point of view, which one can voluntarily choose to miss?